Biodegradability of a bioplastic film from tamarind xyloglucan in composting bioreactors - Paola Andrea Alvarez-Betancourt; Víctor Manuel Luna-Pabello; Jaime Eddy Ussa-Garzón; Alfredo Maciel-Cerda (Dyna, 2021)
Plastic is used excessively due to its excellent properties and its low cost. This has led to the ubiquitous accumulation of waste as it takes a very long time to biodegrade. Until now, several research projects have developed different biodegradable plastics, and the tests to validate them are still being undertaken. In this research, a biodegradability test was performed on a bioplastic synthesized from tamarind xyloglucan and ethyl acrylate (b-XgT), designed to be a substitute for polystyrene. A sample of the b-XgT was composted in laboratory conditions and CO2 release measurements were made. The results showed a biodegradation time of 18 days with a loss of mass of 40.3% and a final pH of 7.1. The b-XgT was found to be biodegradable of the compostable type through the anaerobic route, which promotes the digestion of compounds such as xylose that contribute to the degradation of the whole polymer.